Chondrogenic potential of physically treated bovine cartilage matrix derived porous scaffolds on human dermal fibroblast cells - Moradi, A.; Ataollahi, F.; Sayar, K.; Pramanik, S.; Chong, P.P.; Khalil, A.A.; Kamarul, Tunku; Pingguan-Murphy, Belinda (John Wiley & Sons, 2015)
Extracellular matrices have drawn attention in tissue engineering as potential biomaterials for scaffold fabrication because of their bioactive components. Noninvasive techniques of scaffold fabrication and cross-linking treatments are believed to maintain the integrity of bioactive molecules while providing proper architectural and mechanical properties. Cartilage matrix derived scaffolds are designed to support the maintenance of chondrocytes and provide proper signals for differentiation of chondroinducible cells. Chondroinductive potential of bovine articular cartilage matrix derived porous scaffolds on human dermal fibroblasts and the effect of scaffold shrinkage on chondrogenesis were investigated. An increase in sulfated glycosaminoglycans production along with upregulation of chondrogenic genes confirmed that physically treated cartilage matrix derived scaffolds have chondrogenic potential on human dermal fibroblasts.